Cycloxaprid: a novel cis‐nitromethylene neonicotinoid insecticide to control Bemisia tabaci. Issue 5 (20th December 2019) - Cui, Li; Wang, Qiyuan; Wang, Qinqin; Wang, Li; Yuan, Huizhu; Rui, Changhui
Abstract: BACKGROUND: Bemisia tabaci is a worldwide insect pest with high ability to develop resistance to many insecticides. Cycloxaprid is a novel cis ‐configuration neonicotinoid insecticide that is effective against a wide range of imidacloprid‐resistant pests. RESULTS: The lethal and sublethal effects of cycloxaprid on B. tabaci B were estimated. Cycloxaprid showed higher toxicity against adult, nymph and egg of B. tabaci B than imidacloprid. And cycloxaprid provided better efficacies against B. tabaci than imidacloprid in fields. Moreover, cycloxaprid was similarly toxic to the relatively susceptible and imidacloprid‐resistant populations . The LC50 of cycloxaprid against the resistant adult, nymph and egg were 6.2, 11.5 and 111.3 mg L −1, respectively, while they were 5.7, 8.9 and 129.4 mg L −1 for the susceptible population. In addition, when resistant adult of B. tabaci B was treated with LC30 of cycloxaprid (3.2 mg L −1 ), the net reproductive rate and female ratio of F1 generation B. tabaci were reduced. Moreover, the age‐specific fecundity demonstrated the highest fecundity sharply decreased in cycloxaprid (7.0 offspring/ day) treated group compared with the control (26.0 offspring/ day). CONCLUSIONS: Our results indicated that cycloxaprid is a promising insecticide for the management of B. tabaci and insecticide‐induced resurgence might not occur after exposure of B. tabaci to low sublethal concentrations of cycloxaprid. © 2019 Society of Chemical Industry Abstract : There is a need for estimating the toxicity of cycloxaprid against Bemisia tabaci . This article presents the lethal and sublethal effects of cycloxaprid on imidacloprid‐resistant B. tabaci .